2022
DOI: 10.3389/fgene.2022.949989
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Pulmonary sarcomatoid carcinoma complicating TP53 mutation treated successfully with Tislelizumab combined with Anlotinib—a case report

Abstract: Pulmonary sarcomatoid carcinoma (PSC) is a rare subtype of lung malignant tumor. Conventional chemotherapy has a suboptimal effectiveness. PSC has the characteristics of rapid disease progression and poor prognosis. We herein report a 56-year-old male patient with substantial smoking history was pathologically diagnosed as PSC, cT4N0M0 IIIA stage. Peripheral blood NGS showed TP53 mutation. The patient had poor tolerance to the first-line chemotherapy regimen “albumin paclitaxel + cisplatin,” but the severe ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Doomblides, C et al showed a report on LSC that patients with high TMB had a median OS of 18 months, while the low TMB population had only 1.84 months (49). Other case reports of sarcomatoid carcinoma have also shown a longer survival time with a higher TMB (32,43,37,38).The median value of TMB in patients with sarcomatoid carcinoma of the head and neck was 4.34 (0.71-14.71) muts/Mb, and TMB was significantly higher in patients with advanced stages compared to those with early stages (20). However, the relationship between TMB and immunotherapy in patients with sarcomatoid carcinoma of the head and neck has not been confirmed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Doomblides, C et al showed a report on LSC that patients with high TMB had a median OS of 18 months, while the low TMB population had only 1.84 months (49). Other case reports of sarcomatoid carcinoma have also shown a longer survival time with a higher TMB (32,43,37,38).The median value of TMB in patients with sarcomatoid carcinoma of the head and neck was 4.34 (0.71-14.71) muts/Mb, and TMB was significantly higher in patients with advanced stages compared to those with early stages (20). However, the relationship between TMB and immunotherapy in patients with sarcomatoid carcinoma of the head and neck has not been confirmed.…”
Section: Discussionmentioning
confidence: 97%
“…reported sustained remission in patients with advanced LSC through the application of apatinib in combination with chemotherapy ( 53 ). In addition, anlotinib has exhibited positive clinical outcomes in patients with LCS ( 32 , 43 ). Anlotinib, a new oral tyrosine kinase inhibitor (TKI), targets platelet-derived growth factor receptor, fibroblast growth factor receptor, and vascular endothelial growth factor receptor.…”
Section: Discussionmentioning
confidence: 99%
“…For advanced NSCLC, chemotherapy nonetheless retains an indispensable role. However, several cases suggest that PSC is insensitive to chemotherapy ( 58 , 107 - 109 ).…”
Section: Clinical Characteristics and Treatmentmentioning
confidence: 99%
“…In some case reports, antiangiogenic therapy combined with immunotherapy provided promising results. A chemoresistant patient achieved CR over 20 months after treatment with tislelizumab plus anlotinib ( 109 ). Similarly, good efficacy was observed in cases treated with anlotinib combined with nivolumab ( 155 ), camrelizumab ( 156 ), or pembrolizumab ( 157 ).…”
Section: Clinical Characteristics and Treatmentmentioning
confidence: 99%
“…One study showed that patients with PSC treated with chemotherapy combined with immunotherapy as first-line therapy achieved an objective response rate (ORR) of 73.8% and a median progression-free survival (mPFS) of 10.3 months (6). There are also some case reports that the use of targeted drugs significantly alleviates disease and even survival benefits in patients with PSC (7)(8)(9). Thus, immunotherapy and targeted therapy may offer new opportunities for the treatment of PSC.…”
Section: Introductionmentioning
confidence: 99%